(untitled) (Bangladesh Medical Journal, 2014)
Tetanus Toxoid (TT) is a routine vaccination activity under Expanded Program on Immunization (EPI) in Bangladesh. The women of reproductive age (15-49 years) are the target population for five doses of TT vaccine to protect them from tetanus. The study was a cross-sectional study in context of a rural community. The study was conducted to assess TT vaccination coverage among the women of reproductive age in a rural community of Bangladesh. A total of 224 women of reproductive age were randomly included in the study following selection criteria. Data was collected by recall history and reviewing immunization card by using a semi-structured questionnaire and checklist respectively. Data was processed and analyzed considering both descriptive and inferential statistics. Mean age of the women was 27.22 ± 6.87 years and major part (30.4%) was illiterate. Most of the women were married (87.6%) and housewives (81.3%). Mean age at marriage was 17+2.37 years and mean age at first child birth was 18+2.24 years. On the basis of recall history and vaccination card, 83.5% women received first dose of TT (TT1), while 16.5% didn’t receive any TT vaccine. Among the women received all five doses of TT, ’Crude Vaccination Rate" was 37.0% and ’’Valid Vaccination Rate’ was 33.0%. By card, these rates were 18.5% and 14.2% respectively. The invalid doses found 6.2% for TT2, 7.3% for TT3, 12.5% for TT4 and the lowest 10.8% for TT5 dose. The dropout rate was 5.3% for TT1-TT2, 14.7% for TT2-TT3, the highest 31.1% for TT3-TT4 and 20.2% for TT4-TT5 while 55.6% was for TT1-TT5. Vaccination coverage was significantly higher among the women aged 25-29 years (91.0%) and having HSC level education (92.3%) (x2 test, p<0.05). An incredible segment of rural women didn’t receive any dose of TT5 vaccine and dropout rate was significantly higher among poor and illiterate women. Painstaking interventions and strategies should be taken to increase TT5 vaccination coverage among the rural women to protect them from tetanus. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18780 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 37-41